Are There Advantages to Believing in Fate? The Belief in Negotiating With Fate When Faced With Constraints - Au, Evelyn W. M.; Savani, Krishna (Frontiers in Psychology, 2019)
Is cultural knowledge is unique to a culture and inaccessible to other cultures, or is it a tool that can be recruited by individuals outside of that culture when the situation renders it relevant? As one test of this idea, we explored whether the applicability and benefits of a lay belief that originated from Chinese collective wisdom extends beyond cultural boundaries: negotiating with fate. Negotiating with fate postulates that fate imposes boundaries within which people can shape their outcomes through their actions. This belief contrasts fatalism, which has been traditionally interpreted as believing that fate dictates people’s life outcomes and renders their actions largely irrelevant. We found that the belief in negotiating with fate (but not fatalism) was strengthened when individuals recalled instances in which they were constrained, compared to when individuals recalled instances in which they were free to choose (Experiments 1 and 2). Subsequent studies found that after recalling a constraining event, exposure to the belief in negotiating with fate (but not exposure to fatalism) decreased repetitive thoughts (Experiment 3), increased the conviction that personal actions contributed to the event (Experiment 4), increased acceptance and positive reinterpretation of the event (Experiment 5), and increased how meaningful the event was (Experiment 6). Thus, when faced with constraints, acknowledging fate does not necessarily lead people to believe that their actions are irrelevant. Instead, when individuals face constraining circumstances in which potential courses of actions are clearly limited, they are more likely to believe that they are able to negotiate with fate, and this belief can help them move forward from negative outcomes. We found that the belief in negotiable fate, although originating from Chinese folk culture, is spontaneously activated when people experience constraints even in a non-Chinese culture, and helps people cope with those constraints.